INTEGRATED AGRO MONITORING AND PROTECTION SYSTEM FOR FARMERS - Savita Soma; Rahul Nidode; Vaishnavi Mudbale; Akshata Janwadkar (International Educational Journal of Science and Engineering, 2026)
Agricultural productivity is often affected by animal interference and inefficient water usage. This work introduces a smart farming solution integrating Internet of Things (IoT) devices with data-driven techniques to enhance crop safety and irrigation efficiency. Sensors continuously monitor field conditions such as soil moisture, rainfall, and movement near crops. When unusual activity is detected, alert systems and deterrent mechanisms are activated automatically. Additionally, intelligent data analysis assists in optimizing irrigation schedules based on environmental conditions. The proposed system minimizes manual effort, improves water conservation, and increases overall farming efficiency.